2016
DOI: 10.1017/s175173111600015x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between ovulation rate and embryonic and placental characteristics in multiparous sows at 35 days of pregnancy

Abstract: The objective of this study was to investigate relationships between ovulation rate (OR) and embryonic and placental development in sows. Topigs Norsvin ® sows (n = 91, parity 2 to 17) from three different genetic backgrounds were slaughtered at 35 days of pregnancy and the reproductive tract was collected. The corpora lutea (CL) were counted and the number of vital and non-vital embryos, embryonic spacing (distance between two embryos), implantation length, placental length, placental weight and embryonic wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…On the other hand, Finnsheep (63%) and F1 cross (48%) had a remarkably low embryo survival rate. While these findings are based on fewer animals, the results are in agreement with earlier studies [39,40] where typically higher litter size is associated with higher embryo mortality and vice versa. It would be of great interest to determine if productivity follows the same pattern in F2 (i.e., F1 × F1) crosses, backcrosses and presumably also in a reciprocal cross.…”
Section: Phenotypic Observationssupporting
confidence: 92%
“…On the other hand, Finnsheep (63%) and F1 cross (48%) had a remarkably low embryo survival rate. While these findings are based on fewer animals, the results are in agreement with earlier studies [39,40] where typically higher litter size is associated with higher embryo mortality and vice versa. It would be of great interest to determine if productivity follows the same pattern in F2 (i.e., F1 × F1) crosses, backcrosses and presumably also in a reciprocal cross.…”
Section: Phenotypic Observationssupporting
confidence: 92%
“…That current high ovulation rates indeed affect embryo survival and embryo quality has recently been corroborated by Da Silva et al. (), Da Silva, Broekhuijse, et al. (), for sows and gilts, respectively.…”
Section: Selection On Litter Sizementioning
confidence: 64%
“…In both their study and the study of Da Silva et al. () with sows, these effects on the embryo‐placental units were related to the level of late embryonic mortality, indicating that high ovulation rates combined with uterine crowding compromises the development of the remaining embryo‐placental units.…”
Section: Selection On Litter Sizementioning
confidence: 73%
See 1 more Smart Citation
“…An alternative effect of selection for lower rates of IUGR may be more evenly spaced embryos. Lents et al [ 69 ] reported negative relationships of ovulation rate with embryonic spacing and with empty space around the embryonic-placental unit, which both indicate crowded uterine conditions. Other studies have shown that mouse lines that lack lysophosphatidic acid, a phospholipid involved in uterine peristaltic movements that facilitate embryo separation [ 69 ], have blastocysts that remain clustered in the vicinity of the cervix, whereas non-deficient lines have blastocysts that are evenly distributed along the uterine horns [ 70 ].…”
Section: Discussionmentioning
confidence: 99%